Analisis dan Perancangan Sifo Penjualan, Pembelian, dan Persediaan pada Toko Sepatu Jovi - Siregar, Ade Fatma; Utama Sembiring, Afen Prana (Jurnal Penelitian Multidisiplin Ilmu, 2024)
The rapid development of information systems has a very important role for every company. Jovi Shoe Shop is a shop engaged in the field of shoes which in managing all transactions still uses the method of recording in books and paper media which is still not computerized. The purpose of this research is to design a sales, purchase and inventory information system for this store. The system development methodology used is the System Development Life Cycle (SDLC) methodology. System output design using Crystal Report, system input design using Microsoft Visual Studio 2015, and data storage using Microsoft SQL Server 2014. The result of this writing is the design of an information system that if developed can process, store, and display all sales, purchase, and inventory transactions, and can produce reports that are appropriate to the needs of the store whose purpose if developed is to make it easier for the owner to see and make decisions for the benefit and progress of the store. Translated with DeepL.com (free version)